Regulation of the Forkhead Transcription Factor AFX by Ral-Dependent Phosphorylation of Threonines 447 and 451 - De Ruiter, Nancy D. (American Society for Microbiology, 2001)
AFX is a Forkhead transcription factor that induces a G(1) cell cycle arrest via upregulation of the cell cycle inhibitor p27(Kip1). Previously we have shown that protein kinase B (PKB) phosphorylates AFX causing inhibition of AFX by nuclear exclusion. In addition, Ras, through the activation of the RalGEF-Ral pathway, induces phosphorylation of AFX. Here we show that the Ras-Ral pathway provokes phosphorylation of threonines 447 and 451 in the C terminus of AFX. A mutant protein in which both threonines are substituted for alanines (T447A/T451A) still responds to PKB-regulated nuclear-cytoplasmic shuttling, but transcriptional activity and consequent G(1) cell cycle arrest are greatly impaired. Furthermore, inhibition of the Ral signaling pathway abolishes both AFX-mediated transcription and regulation of p27(Kip1), while activation of Ral augments AFX activity. From these results we conclude that Ral-mediated phosphorylation of threonines 447 and 451 is required for proper activity of AFX-WT. Interestingly, the T447A/T451A mutation did not affect the induction of transcription and G(1) cell cycle arrest by the PKB-insensitive AFX-A3 mutant, suggesting that Ral-mediated phosphorylation plays a role in the regulation of AFX by PKB.